Electron ionisation of cyanoacetylene: ionisation cross sections and dication formation. (15th June 2022) - Ellis-Gibbings, Lilian K; Cooper, Bridgette; Tennyson, Jonathan; Price, Stephen D
Abstract: Cyanoacetylene (HC3 N) is an important trace species in the atmosphere of Titan. We report, for the first time, absolute partial electron ionisation cross sections and absolute precursor-specific partial electron ionisation cross sections for cyanoacetylene, following an experimental and computational investigation. Our methodology involves using 2D ion–ion coincidence mass spectrometry to generate relative cross sections, over the electron energy range 50–200 eV. These relative values are then normalised to an absolute scale, using a binary encounter-Bethe (BEB) calculation of the total ionisation cross section. The BEB calculation agrees well with previous determinations in the literature. The mass spectrometric observations of HC2 N + and HCN +, ions with a connectivity markedly different to that of the neutral molecule, point towards a rich cationic energy landscape possessing several local minima. Indeed, [HC3 N] 2+ minima involving a variety of cyclic configurations are revealed by a preliminary computational investigation, along with two minima with linear and bent geometries involving H atom migration (CCCNH 2+ ). Determination of the energy of a transition state between these local minima indicates that the dication is able to explore the majority of this rich conformational landscape at our experimental energies. This investigation of the energetics also determines an adiabatic double ionisation energy of 30.3 eV for the lowest lying singlet state of HCCCN 2+, and 30.1 eV for the lowest-lying triplet state. The bulk of the cation pairs detected in the coincidence experiment appear to originate from markedly excited dication states, not the ground state. We observe 5 two-body dissociations of HCCCN 2+, and subsequent decay of one of the ions generated in such two-body processes accounts for the majority of three-body dissociations we observe.